Effect of Core Competence and Brand Personality of Short Video Websites on User Loyalty - Wei Cui; Kai Liao; Zi-yang Liu* (Tehnički Vjesnik, 2019)
Influenced by the strong demand for fragmented entertainment from network users, the short video industry has entered an unprecedented period of rapid development, but any emerging industry goes through a life cycle. The purpose of this article is to explore the impact of core competitiveness and brand personality on user loyalty in short video industry by using questionnaire survey for Chinese short video users and statistical analysis based on survey data, so as to provide suggestions for short video websites to improve user loyalty and prolong life cycle. Core competitiveness and brand personality are considered as independent variables, user perceived value characteristics as the moderator variable, and user loyalty as the dependent variable to construct the research model. The SPSS and AMOS statistical analysis tools are applied to reliability analysis, validity analysis, and structural equation model analysis of the survey data. The Results show that the core competitiveness of the short video industry has no positive effect on user perceived value; and the brand personality has a significant positive impact on the user perceived value; the core competitiveness of the short video industry has a significant positive impact on the user loyalty; the brand personality has a significant positive impact on the user loyalty; and the user perceived value has a significant positive impact on the user loyalty. Based on the above results, we suggest the short video website improve its core competitiveness through creating original videos, and adopting diversified content production modes, using network transmission and mass media to promote short video products, so as to strengthen the brand communication, shape the brand image and enhance the user perceived value, etc.